2010
DOI: 10.1007/s11032-010-9527-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mesoamerican intra-genepool genetic map for quantitative trait loci detection in a drought tolerant × susceptible common bean (Phaseolus vulgaris L.) cross

Abstract: Drought is a major constraint to common bean (Phaseolus vulgaris L.) production, especially in developing countries where irrigation for the crop is infrequent. The Mesoamerican genepool is the most widely grown subdivision of common beans that include small red, small cream and black seeded varieties. The objective of this study was to develop a reliable genetic map for a Mesoamerican × Mesoamerican drought tolerant × susceptible cross and to use this map to analyze the inheritance of yield traits under droug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 45 publications
16
112
0
8
Order By: Relevance
“…In this context, the increased population growth combined with climate change and the need for food production on a large scale will require the cultivation of plants more adapted to stress conditions (McClean et al, 2011). Upon the intensification of a biotic stresses, several research groups on the genetic improvement of beans have implemented multidisciplinary programs to analyze a biotic stresses aimed at identifying drought tolerant genotypes, exploring their genetic variability, such as early maturity, deep rooting for greater absorption of water, physiological adaptation through stomatal conductance, along with satisfactory grain yield in stressed crops (Blair et al, 2012). Singh et al (2001) registered the line SEA 5 as a drought tolerant cultivar, derived from interracial crosses between the races Mesoamerican and Durango, and one of the parents originating the line was the cultivar BAT 477, also described by the authors as drought tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the increased population growth combined with climate change and the need for food production on a large scale will require the cultivation of plants more adapted to stress conditions (McClean et al, 2011). Upon the intensification of a biotic stresses, several research groups on the genetic improvement of beans have implemented multidisciplinary programs to analyze a biotic stresses aimed at identifying drought tolerant genotypes, exploring their genetic variability, such as early maturity, deep rooting for greater absorption of water, physiological adaptation through stomatal conductance, along with satisfactory grain yield in stressed crops (Blair et al, 2012). Singh et al (2001) registered the line SEA 5 as a drought tolerant cultivar, derived from interracial crosses between the races Mesoamerican and Durango, and one of the parents originating the line was the cultivar BAT 477, also described by the authors as drought tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators also have observed significant differences in the traits DFL, DH, ARQ, PROD, H, J, and M100 in common bean. Blair et al (2012) reported significant effects for DFL, DH, PROD, and M100, in 113 RILs derived from parents belonging to the same Mesoamerican gene pool. Faleiro et al (2003) investigated 154 RILs derived from a cross between Ouro Negro and Rudá (both from the Mesoamerican gene pool) and found significant effects for the traits DFL, DH, and M100.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, seeds of these RILs are not readily available. Another mapping population was developed by Blair et al (2012) and comprises 113 RILs derived from a cross between DOR 364 and BAT 447; both parents belong to the Mesoamerican gene pool. The small size of this population is a limitation; moreover, the availability of seeds for exchange and use by different teams is low.…”
Section: Introductionmentioning
confidence: 99%
“…Drought field trials performed with the RIL population of the crossing BAT 477 × DOR 364, previously referred to the greenhouse experiment, showed significant variability across four locations evaluated [104]. A QTL analysis associating the field traits to a previous set of molecular markers disposed in a linkage map [106] showed significant QTL-environment interactions. Therefore, determining if one cultivar is tolerant to drought does not necessarily mean it will respond well to all environments, in a sense that it must be tested in multiple environments to check for its performance.…”
Section: Phenotyping For Drought Tolerance In Common Beanmentioning
confidence: 93%